Trade policy, income risk, and welfare - Krebs, Tom; Krishna, Pravin 1969-; Maloney, William F. 1959- (National Bureau of Economic Research, 2005)
"This paper studies empirically the relationship between trade policy and individual income risk faced by workers, and uses the estimates of this empirical analysis to evaluate the welfare effect of trade reform. The analysis proceeds in three steps. First, longitudinal data on workers are used to estimate time-varying individual income risk parameters in various manufacturing sectors. Second, the estimated income risk parameters and data on trade barriers are used to analyze the relationship between trade policy and income risk. Finally, a simple dynamic incomplete-market model is used to assess the corresponding welfare costs. In the implementation of this methodology using Mexican data, we find that trade policy changes have a significant short run effect on income risk. Further, while the tariff level has an insignificant mean effect, it nevertheless changes the degree to which macroeconomic shocks affect income risk"--National Bureau of Economic Research web site.
Keywords: Ökonometrisches Modell; Commercial policy -- Economic aspects; Labor market -- Econometric models; Mexiko; Mexico -- Commercial policy